Dealing with digital intermediaries: A case study of the relations between publishers and platforms - Kleis Nielsen, R; Ganter, S (SAGE Publications, 2017)
The rise of digital intermediaries such as search engines and social media is profoundly changing our media environment. Here, we analyze how news media organizations handle their relations to these increasingly important intermediaries. Based on a strategic case study, we argue that relationships between publishers and platforms are characterized by a tension between (1) short-term, operational opportunities and (2) long-term strategic worries about becoming too dependent on intermediaries. We argue that these relationships are shaped by news media’s fear of missing out, the difficulties of evaluating the risk/reward ratios, and a sense of asymmetry. The implication is that news media that developed into an increasingly independent institution in the 20th century—in part enabled by news media organizations’ control over channels of communication—are becoming dependent upon new digital intermediaries that structure the media environment in ways that not only individual citizens but also large, resource-rich, powerful organizations have to adapt to.